The Analysis of Guided Inquiry Learning Model to XI Grader’s Motivation on Thermochemistry - Azzachra, Alya Shifa Shifa; Hidayah, Fitria Fatichatul Fatichatul (LAVOISIER: Chemistry Education Journal, 2024)
Consistent learning is generally based on great curiosity, a drive of need or pressure that makes one inevitably have to recognise new things. The consistency of student learning ultimately requires the main driver commonly referred to as learning motivation. In addition to student learning motivation, careful learning preparation with the application of interesting learning models can be another success factor in education, one of these learning models is the guided inquiry model. The research method used is qualitative with a descriptive approach. The research subject chosen was class XI students in one of the high schools in Semarang City and the sample was all class XI students totalling 36 students consisting of 15 male students and 21 female students, with an age range of 16-18 years. The object of the research is the analysis of guided inquiry learning model on the interest in learning chemistry, especially thermochemistry material. The results showed that 47.2% of students strongly agreed that they had learnt many thermochemistry materials related to daily life. 61.1% of students strongly agree that they have applied the concept of thermochemistry in everyday life, for example by heating water, cooling water, and so on. 30.6% of students disagreed that they had difficulties in learning chemistry materials related to daily life. 91.7% of students answered that learning in the laboratory can maintain their interest in learning, especially in thermochemistry material. Therefore, this guided inquiry learning model is effective to maintain students' learning motivation supported by laboratory facilities.